PkM Pelatihan Literasi Keuangan untuk Meningkatkan Kompetensi Diri Santri di Pondok Pesantren Al-Jihad Surabaya - Riska Ayu Setiawati; Helmina Ardyanfitri (Universitas Nurul Jadid, 2023)
Based on data released by OJK in 2019, Indonesia's financial literacy index is still 38.03% well literate, where a country's financial literacy can support economic growth so that a lack of financial literacy will become a problem in the environment, especially in Islamic boarding schools, one of which is at the AlJihad Islamic Boarding School, Surabaya. This study aims to educate financial literacy in Islamic boarding schools. The method used is the Service Learning (SL) method, which is a community empowerment method that integrates academic activities into community empowerment which in turn provides an opportunity to actualize the integration of academic knowledge and problems in society. The community service is carried out for three days on December 9-11, 2022 for three to four hours, with one speaker from outside. The materials trained are Personal finance management, savings and loans, risk management and insurance, and investment. The implementation of community service went well, and based on the results of the pre-test before being given training, the financial literacy of students was low and the index was less literate, and after being given financial education the level of financial literacy became moderate and the index increased from the previous less literate to sufficient literate based on the OJK index, which means that students have an understanding and confidence about financial service institutions and financial products and services, including features, benefits and risks, rights and obligations related to financial products and services, but do not yet have skills in using financial products and services. Skills in using can be improved if students have earned their own income and can fully manage their finances.